BENTUK HUBUNGAN PERS DENGAN PEMERINTAH TERKAIT DENGAN FUNGSI MEDIA SEBAGAI KONTROL SOSIAL - Venezia Indra Ghassani; Praptining Sukowati (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
The relationship between the press and the government is symbiotic mutualism. A relationship that is mutually beneficial. Expected media as partners are able to socialize development program to provide insight to the community on any public policy undertaken by the local government. It is therefore important for a government to have a good relationship with the mass media in order to convey information about government activities properly. Press is expected in reporting can be a friend of the community through preaching constructive (building), accurate, balanced, and not defamatory and comply with the code of ethics of Indonesia journalists.DOI: https://doi.org/10.26905/pjiap.v1i2.502